The Georgian History of the Strand Lane 'Roman' Bath. (July 2014) - Trapp, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> Among its several identities, the Strand Lane 'Roman Bath' is the last Central London survivor of the city's Georgian and Regency cold plunge baths. Using a combination of documentary and archaeological evidence, this paper traces the story of its conversion to this function in the last quarter of the eighteenth century, identifies the probable author of the conversion, reconstructs its eighteenth-century form and layout, and discusses the context in which the conversion took place.